Clinical Study Of Charakokta Arshoghna Mahakashya In Suskh Arsh. - Sharma, Sheetal (International Research Journal of Ayurveda & Yoga, 2020)
WHO has started celebrating the 20th November of each year as world piles day with an intention of spreading the awareness of piles. Piles are one of the most common problem of rectum affecting both men & women. It clearly indicates the infestation of this disease all over the world and tremendous physical and mental suffering of mankind as a result of disease. Acharaya Charak has explained fifty Mhakasaya in Charak Sanhita Sutrasthan-4 and one of the Mahakasayas is Arshoghan Mahakasaya present study is carried out using ten drugs of Arshoghan Mahakasaya and their efficacy in breaking the pathology of Suskh Arsh.